Introduction of Innovations in the Tourism Industry: Experience of Ukraine - Alla Donysche-Medyanik; Mykhaylo Klyap (Studia Universitatis Vasile Goldis Arad, Seria Stiinte Economice, 2017)
The article deals with relevance and necessity of studying innovative processes in tourism industry as an important indicator of tourism development in the modern market conditions. Formulated and substantiated directions of innovative technologies introduction in the hospitality industry of Ukraine. Conducted research and substantiated principles of innovations in tourism and the processes in use of advanced services: Sleepbox, multimedia digital technologies Digital Signage, new technologies “Teleport” from the hotel network “Marriott”. Suggested a few ways to improve the service economy.